Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Framing Goals of Mathematics Support Measures - Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Schürmann, Mirko; Biehler, Rolf; Schaper, Niclas (Practice-Oriented Research in Tertiary Mathematics Education)

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Piloteinsatz einer E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo

Participative human-factor evaluation in the context of digital work (re-)design - Schumacher, Jan-Philip; Depenbusch, Sarah; Straatmann, Tammo; Bender, Elena; Schaper, Niclas; Hamborg, Kai-Christoph (Work)
BACKGROUND: Challenged by digital transformation, organizations increasingly integrate information and communication technologies into work designs. Often focal points of such digital reengineering initiatives are technical and economic aspects. Yet, as integration of new technologies affects how employee work and interact, there is a need to evaluate human-centered criteria (human-factor evaluation), optimally by involving employees as situational experts. OBJECTIVE: The present study develops an integrative and persona-based evaluation approach of human-centered criteria for application in participative digital (re-)design of work to support the joint optimization of the technical and social system. METHODS: Drawing on methods from usability evaluation, a persona-based approach is developed to facilitate comprehension and application of human-centered evaluation by employees. To that end, human-centered criteria from existing evaluation models are systemized with specific reference to digital transformation of work processes. The developed approach is tested in pilot runs of three German small and medium-sized enterprises (SMEs). RESULTS: The initial overview shows a divergence of specific human-centered criteria at the detailed level. Simultaneously, a high convergence is found for overarching dimensions and categories. The Integrative Socio-Digital Evaluation Model (ISDEM) is developed to balance complexity and abstraction of criteria. The derived persona-based approach (persISDEM) shows a good applicability in the pilot runs. CONCLUSIONS: The present study provides an amendment to existing work design approaches with an emphasis on employee participation, enabling organizations to foster employees’ comprehension and motivation to engage in evaluations of digital (re-)design of work and to create motivating and healthy jobs for successful digital transformation.
Keywords: Public Health; Environmental and Occupational Health; Rehabilitation

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Die Health Professionals Competence Scales (HePCoS) zur Kompetenzerfassung in den Gesundheitsfachberufen. Technical Report - Grebe, Christian; Schürmann, Mirko; Latteck, Änne-Dörte

Die Rolle von arbeitsplatzbezogener Flexibilisierung und die Betrachtung von individuellen Werten für Mitarbeitendenbindung in der Arbeitswelt 4.0 - Bender, Elena; Schürmann, Mirko; Poethke, Ute; Soyka, Chantal; Schaper, Niclas; Rowold, und Jens (Zeitschrift für Arbeits- und Organisationspsychologie A&O)
Zusammenfassung. In der Arbeit 4.0 ist durch neue Beschäftigungsmöglichkeiten für Mitarbeitende eine Langzeitbindung an ein Unternehmen seltener. Unternehmen reagieren mit flexibilisierten Arbeitsplätzen, um diesem Wunsch der Mitarbeitenden nachzukommen. Flexibilisierung reduziert die Absicht das Unternehmen zu verlassen. Dabei ist wichtig, räumliche und zeitliche Flexibilisierung zu differenzieren. Außerdem gewinnen individuelle Werte bezüglich Stabilität und Kontinuität an Bedeutung und können den Bindungswunsch stärken. Hauptziel dieser Untersuchung ist, anhand eines kontroll- und ressourcentheoretisch fundierten Rahmens in zwei aufeinander aufbauenden Studien ( N = 448, N = 202) die (potenziell unterschiedlich starken) Zusammenhänge von zeitlicher und räumlicher Flexibilisierung mit Mitarbeitendenbindung zu analysieren und zu prüfen, ob sich diese Zusammenhänge bestätigen lassen, wenn zusätzlich individuelle Werte in die Analyse einbezogen werden. Die Ergebnisse zeigen, dass zeitliche und räumliche Flexibilisierung unterschiedlich mit der Bleibeabsicht zusammenhängen. Während zeitliche Flexibilisierung positive Zusammenhänge zeigt, finden sich in Bezug auf räumliche Flexibilisierung keine Zusammenhänge. Werte bezüglich Stabilität und Kontinuität scheinen dabei nicht mit einer stärkeren Mitarbeitendenbindung zusammenzuhängen.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

Prospektive und prozessbezogene Kompetenzanalyse - Gestaltung und Erprobung eines Vorgehens - Depenbusch, Sarah; Bender, Elena; Schaper, Niclas

Investigating the multidimensionality of informal learning: Validation of a short measure for white‐collar workers - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (Human Resource Development Quarterly)
Keywords: Organizational Behavior and Human Resource Management; Arts and Humanities (miscellaneous)

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)

Opportunities and Possibilities of a Network of Mathematical Learning and Support Centres in Germany - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (Sigma newsletter)

Mathematics learning support centres in Germany—an overview - Schürmann, Mirko; Gildehaus, Lara; Liebendörfer, Michael; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard; Kuklinski, Christiane; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Mathematics learning support centres (MLSC) are widely established and evaluated in English-speaking countries (such as the UK, Ireland and Australia). In most of these countries, several national surveys on MLSCs exist. They give an overview of the number of MLSCs as well as their characteristics in these countries. In Germany, there is a lack of studies on MLSCs and the landscape of MLSCs has not been described yet. This article presents basic information concerning counts of MLSCs and their characteristics at universities. Based on a three-step approach of analysing university homepages and additional personal contact via email or phone calls, we gathered typical MLSC features (e.g. staff quantities and qualification, opening and support hours, supported study programmes). We analysed 190 universities from a web-based register on study programmes. In total, we found 61 MLSCs located at 51 German universities. Another 16 support centres were specialized on mathematics didactics, which means they focussed on didactical and methodological support for preservice teacher students and often provided different teaching materials. Thirty-eight centres were located at universities (62.3%) and 23 MLSCs at universities of applied sciences and comparable universities (37.7%). The MLSCs were different in their sizes of staff and opening hours, and both the numbers of staff and the service hours differed greatly. The student groups MLSCs at German universities focus on differ concerning characteristics like study programme or semester. We will provide the main categories describing these groups. We seek to answer research questions concerning the characteristics of MLSCs in Germany and discuss the results compared to international findings. This information is useful for further international collaborative research, for example a standardized international survey. From a national perspective, these findings support networking and collaborations between the MLSCs as well. As some German MLSCs are facing financial cuts, these results might help in gaining additional funding.
Keywords: Education; General Mathematics

Chancen und Möglichkeiten eines Netzwerks von Mathematischen Lernzentren in Deutschland - Bericht zum digitalen Lernzentrumsworkshop am 22.10.2020 - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (dghd-Newsletter)

Ein Kurzbericht aus dem Forschungsprojekt WiGeMath-Lernzentren als Unterstützungsmaßnahme für mathematikbezogenes Lernen in der Studieneingangsphase - Schürmann, Mirko; Schaper, Niclas; Liebendörfer, Michael; Biehler, Rolf; Lankeit, Elisa; Hochmuth, Reinhard; Ruge, Johanna; Kuklinski, Christiane (dghd-Newsletter)

Factors Driving Employeesʼ Intention to Stay - Bender, Elena; Schaper, Niclas; Schürmann, Mirko (Zeitschrift für Arbeits- und Organisationspsychologie)
Abstract. This study investigates factors influencing employeesʼ intention to stay. Therefore, we developed and analyzed a retention model relating to the voluntary turnover model ( Allen et al., 2010 ). We assume that the decision processes for retention and turnover might be similar. Differences can be found in the initiating factors (the drivers for leaving and staying). We combine empirically evident retention drivers, which are weighted regarding their implementation in the organization, with process variables from the turnover model. The model is tested with a sample of 881 German employees using structural equation modeling. Results show a significant indirect effect of the retention drivers on the intention to stay. The influence is mediated by the key attitudes job satisfaction and affective commitment. A psychological contract breach influences the relationship between job satisfaction and intention to stay, but not between affective commitment and intention to stay. We integrated research from Human Resource Management (HRM) into the framework of voluntary turnover.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

Features of innovative lectures that distinguish them from traditional lectures and their evaluation by attending students - Kuklinski, Christiane; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Lankeit, Elisa; Leis, Elena; Schürmann, Mirko (Proceedings of CERME 11)

Verbundprojekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Kuklinski, Christiane; Lankeit, Elisa; Leis, Elena; Liebendörfer, Michael; Schürmann, Mirko (3. Auswertungsworkshop der Begleitforschung. Dokumentation der Projektbeiträge.)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathmatikbezogenes Lernen in der Studieneingangsphase : Schlussbericht: Teilprojekt A der Leibniz Universität Hannover, Teilprojekte B und C der Universität Paderborn: Berichtszeitraum: 01.03.2015-31.08.2018 - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Kuklinski, Christiane; Lankeit, Elisa; Leis, Elena; Liebendörfer, Michael; Schürmann, Mirko

A framework for goal dimensions of mathematics learning support in universities - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Kuklinski, Christiane; Khellaf, Sarah; Colberg, Christoph; Schürmann, Mirko; Rothe, Lukas (Proceedings of the Tenth Congress of the European Society for Research in Mathematics Education (CERME10, February 1 – 5, 2017))
Keywords: Ziele der Lehre

Projekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Schürmann, Mirko; Biehler, Rolf; Hochmuth, Reinhard Karl; Schaper, Niclas; Liebendörfer, Michael (Working Paper Studieneingangsphase Perspektiven aus der Begleitforschung zum Qualitätspakt Lehre)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Liebendörfer, Michael; Schürmann, Mirko (Beiträge zum Mathematikunterricht 2016)